Low cyclic loading tests and fatigue damage models of concrete bridge piers reinforced with high-strength rebar. Issue 4 (March 2021) - Zhuo, Wei-ding; Wu, Suiwen; Liu, Zhao; Zang, Hua
Reinforced concrete bridge piers are extremely vulnerable to damage during long-duration ground excitations or main shock-aftershock type earthquakes due to accumulated damage caused by a great number of reversed excursions in elastic-plastic range. However, few studies on fatigue damage of piers can be found in literature. Low-cyclic loading tests of four identical RC bridge piers with high-strength rebar HRB600E (yield strength about 600 MPa) were carried out in this study. One of specimens was taken as the benchmark and was subjected to a conventional load protocol, and the rest was subjected to one, two and three times yield displacement, respectively. The research results showed that the fatigue strength of RC bridge piers tended to drop drastically at about ten cycles and then slowed down gently. It was found that strength degradation rate increased significantly with the displacement amplitude for fatigue tests while the fatigue life decreased dramatically with the displacement amplitude. In particular, when the cyclic loading displacement exceeded 2 times the yield displacement, the fatigue life dropped dramatically. Based on the experimental data, an exponential-type damage model was proposed with the peak lateral force at the first cycle as the coefficient, the cycle count as the base and factor of the loading displacement amplitude as the exponent, which could accurately predict the degraded lateral force of the bridge piers at different constant drifts. An accumulative fatigue damage index was established to evaluate the damage level of bridge piers.